Divalent Metal Vinylphosphonate Layered Materials: Compositional Variability, Structural Peculiarities, Dehydration Behavior, and Photoluminescent Properties - Pérez-Colodrero, Rosario Mercedes; Cabeza-Díaz, Aurelio; Olivera-Pastor, Pascual; Choquesillo-Lazarte, Duane; García-Ruíz, Juan M.; Turner, Adele; Ilia, Gheorghe; Maranescu, Bianca; Papathanasiou, Konstantinos E.; Hix, Gary B.; Demadis, Konstantinos D.; García-Aranda, Miguel Ángel (American Chemical Society, 2011)
A family of M-VP (M = Ni, Co, Cd, Mn, Zn, Fe, Cu, Pb; VP = vinylphosphonate) and M-PVP (M = Co, Cd; PVP = phenylvinylphosphonate) materials have been synthesized by hydrothermal methods and characterized by FTIR, elemental analysis, and thermogravimetric analysis (TGA). Their structures were determined either by single crystal X-ray crystallography or from laboratory X-ray powder diffraction data. The crystal structure of some M-VP and M-PVP materials is two-dimensional (2D) layered, with the organic groups (vinyl or phenylvinyl) protruding into the interlamellar space. However, the Pb-VP and Cu-VP materials show dramatically different structural features. The porous, three-dimensional (3D) structure of Pb-VP contains the Pb center in a pentagonal pyramid. A Cu-VP variant of the common 2D layered structure shows a very peculiar structure. The structure of the material is 2D with the layers based upon three crystallographically distinct Cu atoms; an octahedrally coordinated Cu2+ atom, a square planar Cu2+ atom and a Cu+ atom. The latter has an unusual co-ordination environment as it is 3-coordinated to two oxygen atoms with the third bond across the double bond of the vinyl group. Metal-coordinated water loss was studied by TGA and thermodiffractometry. The rehydration of the anhydrous phases to give the initial phase takes place rapidly for Cd-PVP but it takes several days for Co-PVP. The M-VP materials exhibit variable dehydration-rehydration behavior, with most of them losing crystallinity during the process.
Keywords: Química inorgánica; X-ray diffraction; Divalent Metal Vinylphosphonate; Metal phosphonates